PENGARUH DURASI SERANGAN GELOMBANG TERHADAP TINGKAT KERUSAKAN LAPIS LINDUNG PEMECAH GELOMBANG - Ida Bagus Agung (Universitas Sarjanawiyata Tamansiswa, 2015)
this research tetrapod have been utilized for breakwater cover layer or armour layer. The effect of wave duration on the armor layer tetrapod stability was studied. The models were run in the irregular wave flume, where Bretschneider spectrum may be generated attacking the breakwater. The waves were set to break before reaching the breakwater. The test was conducted until the damage level of armour layer reached more than 5 %. The result of the research showed that waves duration and the high of the wave attack affect the stability of armour layer, especially when the wave was Rayleigh distributed. The effect of waves duration reduced as more and more waves broken before reaching the structure of the breakwater